TRP, The Magister student Analysis of Factors Related to Job Satisfaction and Its Relationship with Community Satisfaction - Paramita, Tri Ratna; Adrianto, Ratno; Ramdan, Iwan Muhamad (Preventif : Jurnal Kesehatan Masyarakat, 2025)
The quality of services at RSUD Taman Husada has not met the expected standards, partly due to disparities in employment status affecting compensation and career development. Assessing employee job satisfaction is crucial, as it directly influences service effectiveness and patient satisfaction. This study aimed to describe job satisfaction and community satisfaction at RSUD Taman Husada and to analyze the factors associated with job satisfaction and its relationship to community satisfaction. This study employed a cross-sectional design involving 250 employees at Taman Husada Regional Hospital. Data were collected using a structured questionnaire to assess job satisfaction and community satisfaction. Statistical analyses, including Spearman's rank correlation and logistic regression, were conducted to identify significant factors associated with job satisfaction and its relationship to public satisfaction. The results showed that job satisfaction was categorized as high (78.42), while the community satisfaction index was very good (89.59). Significant factors influencing job satisfaction included achievement, recognition, responsibility, advancement, work itself, compensation, job security, working conditions, organizational policies, technical supervision, and interpersonal relationships (p < 0.005). The most dominant factor was work itself (OR = 16.89). No significant relationship was found between job satisfaction and community satisfaction in the aspect of employee behavior (p = 0.715). It was concluded that intrinsic and extrinsic factors significantly affect job satisfaction. However, a direct relationship with community satisfaction has not been established.